Impacts of surface air temperature variability on agricultural droughts of southern Africa: the case of the Free State Province, South Africa - Mbiriri, Mavis (University of the Free State, 2018)
The Free State Province of South Africa is an agricultural region and a leading producer of food crops, including maize, the staple crop for the country. With the Drakensberg Mountains occupying much of its eastern part, the province does not only have a complex topography but also a highly varied climate. This makes the region, especially the highlands vulnerable to climate change. Increased temperatures are set to enhance the intensity of drought due to a reduction in the availability of water resources for crop farming due to excessive evapotranspiration. But the extent to which the rising temperatures have modified the agricultural droughts in relation to the variability of topography in this region has not yet been assessed. In this study, the impact of surface air temperature (SAT) variability on agricultural droughts in the province is assessed for the period between 1960 and 2013. This is achieved by using two drought indices, the Standardized Precipitation Index (SPI), and the Standardized Precipitation Evapotranspiration Index (SPEI) where the former is based solely on precipitation and the later incorporates the effect of evapotranspiration. Evapotranspiration is driven by a number of variables which include wind speed, radiation, humidity and temperature. The severity and frequency of droughts is expected to increase under climate change that is primarily driven by increased temperatures. The impact of altitude on agricultural drought characteristics is also considered. Gridded monthly precipitation, SAT and SPEI data were extracted from Climate Explorer`s database, while SPIs for individual grid points were calculated using the Drought Indices Calculator (DrinC). In order to characterise drought, the clustering method of Hot-Spot analysis was employed to divide the province into homogenous regions based on altitude. All maps were produced using spatial interpolation techniques in ArcMap V.10.2. The results revealed that although the average total precipitation increases from west to east following increasing altitude, the high-altitude regions have shown higher occurrences of severe droughts (SPI ≤-1.282) in recent years, compared to the low-lying western regions. The differences between adjacent clusters are more pronounced during the early summer sub- season (October-December) than in the late summer sub-season (January-March). The observed spatiotemporal heterogeneity in SPI variability reveals that the factors governing drought interannual variability vary markedly withing the region for the two subseasons. Among these factors is altitude. To ascertain the influence of altitude on agricultural drought, an Analysis of Variance test was performed. The results show a significant relationship between drought severity and altitude during the OND but could not be confirmed for JFM. The impact of altitude is also partly manifested in the strong relationship between meridional winds and SPI extremes. Wet seasons are observed when the winds are northerly and droughts when winds are southerly of the Free State Province. When the winds are largely northerly, Free State lies predominantly in the windward side of the Drakensburg Mountains but lies in the rain shadow when the winds are predominantly southerly. The relationship between El Nino Southern Oscillation and SPI indicates stronger correlations for the early summer sub-season than for the late summer sub-season while on the overall, presenting a diminishing intensity with height over the province. The Sequential Regime Shift Detection (SRSD) was used to test for significant abrupt shifts in the variability of precipitation in the province and results were confirmed by the Cumulative significant positive shift in average SPI, during the OND subseason was detected for the far western low-lying and central regions of the province around the 1990s. Temperature, on the other hand shows a significant abrupt shift around 2003 for maximum temperature (Tmax) during the early sub-season and around 1983 for minimum temperature (Tmin) during the late sub-season. The OND Tmax shift coincides with that in cloud cover, with a strong correlation between the two variables. It is intriguing to note that the significance of temperature change is stronger towards the highland regions, to the north and northwest of the province. This shift in temperature is further investigated to explore the impact it has on the intensification of agricultural droughts in the province. It is concluded that despite the observed significant increase in temperature, SPEI does not reflect any significant effect of temperature on drought intensification. In conclusion therefore, precipitation could be the major determinant of droughts in the Free State Province since there is no significant difference between SPI and SPEI variability. There is need to investigate the role of other factors, that may also contribute to drought intensification in the province; such as humidity, solar radiation and wind speed which may have neutralised the well-known impact of temperature on agricultural drought characteristics of the province.
Thesis (Ph.D. (Geography))--University of the Free State (Qwaqwa Campus), 2018
Keywords: Free State, South Africa; Drought; Climate change; Temperature